Impact of Citrus Essential Oil Diffusion on Health Care Staff's Stress Levels: An Evidence-Based Practice Project. Issue 2 (March 2021) - Reynolds, Staci S.; Hodges, Elyse; Tang, Jessica; Dahnke, Deborah; Thomesen, Emily M.
Abstract : Essential oil diffusion can decrease stress. In one hospital, citrus essential oils were diffused over 6 weeks. Staff completed surveys of their stress levels before and after diffusion. Staff did not report a significant reduction in stress; however, there was an increase in feeling "relaxed."